Efficacy of sport and slow stroke back massage as a non-pharmacological therapy to lower blood pressure in elderly with chronic hypertension - Azmy, Liza Ulil; Subrata, I Made; Suariyani, Ni Luh Putu (Universitas Udayana, 2021)
Background and purpose: The prevalence of hypertension has been increasing along with the increasing elderly population. Non-pharmacological therapies such as sports and slow stroke back massage offer a potential adjuvant therapy for elderly patient with chronic hypertension. This study aims to determine the efficacy of sports and slow stroke back massage as nonpharmacological therapies to lower blood pressure in this age group. Methods: This study was a Parallel Group Randomized Controlled Trial, conducted in Patrang, Jember, East Java. The study involved a total of 72 elderly aged between 60 to 79 years old who had blood pressure of ≥140/90mmHg, and not taking antihypertensive drugs. The study participants were assigned randomly into three groups namely, the sports massage, slow stroke back massage, and control groups. Subject characteristics, stress level, physical activity level and eating habit were collected through structured interview using standardized questionnaires (Global Physical Activity Questionnaire, Food Frequency Questionnaire, Depression Anxiety Stress Scale (DASS 21)). Blood pressure measurements were done twice, before and after treatment. Before and after comparison was conducted with Wilcoxon test, between group comparison was conducted with Kruskal Wallis test followed by Mann Whitney test. Results: The average systolic blood pressures before and after sports massage were 168.96±SD 16.02 mmHg and 147.50±SD 15.95 mmHg, respectively. For the slow stroke back massage was 165.42±12.50 mmHg before treatment and 154.58±16.15 mmHg after treatment. The systolic and diastolic blood pressures before and after treatment in the treatment groups (sports massage and slow stroke back massage) were statistically different from the control group (p <0.05). Further, the Mann Whitney results indicated that slow stroke back massage was more effective than sports massage in lowering blood pressure in elderly with hypertension. Conclusions: Sport massage and slow stroke back massage are effective as a non-pharmacological therapy in lowering blood pressure in elderly with hypertension. These non-pharmacological therapies should be considered for controlling blood pressure in elderly.